2015
DOI: 10.1016/j.sleh.2015.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive sleep apnea and stroke: links to health disparities

Abstract: Obstructive sleep apnea (OSA) is a novel cardiovascular and cerebrovascular risk factor that presents unique opportunities to understand and reduce seemingly intractable stroke disparity among non-Hispanic blacks and Hispanic/Latinos. Individuals from these 2 groups have up to a 2-fold risk of stroke and greater burden of OSA. Obstructive sleep apnea directly and indirectly increases risk of stroke through a variety of autonomic, chemical, and inflammatory mechanisms and vascular risk factors such as hypertens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 66 publications
(66 reference statements)
1
11
0
Order By: Relevance
“…Our findings support prior conclusions that SDB and stroke are highly comorbid, although under-screening and under-diagnosis are common, especially within nonwhite racial and ethnic populations [16][17][18]. Only one patient out of 68 in our cohort had a previous diagnosis of SDB.…”
Section: Discussionsupporting
confidence: 90%
“…Our findings support prior conclusions that SDB and stroke are highly comorbid, although under-screening and under-diagnosis are common, especially within nonwhite racial and ethnic populations [16][17][18]. Only one patient out of 68 in our cohort had a previous diagnosis of SDB.…”
Section: Discussionsupporting
confidence: 90%
“…OSA may lead to stroke through its associations with potent vascular risk factors, such as hypertension, diabetes mellitus, obesity, and atrial fibrillation. OSA may also increase stroke and CVD risk through reduction in cerebral blood flow, altered cerebral autoregulation, impaired endothelial function, increased platelet activation, inflammation, and oxidative stress related to the intermittent hypoxemia–reoxygenation and arousals associated to increased sympathetic tone ( 10 ). The treatment of OSA has been considered an important intervention for reducing the morbidity and mortality associated with stroke and CVD ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, studies have shown that acculturation in the host country might have an impact on the physical health status of immigrants [25]. Chronic illnesses such as obesity, diabetes, and hypertension can in return affect sleep quality [26]. Thirdly, psychosocial factors like socioeconomic status (low education and unemployment), low income, and being unmarried are related to sleep disruption [27].…”
Section: Discussionmentioning
confidence: 99%